STRATEGI PENGEMBANGAN OBJEK WISATA PANTAI PENIMBANGAN KABUPATEN BULELENG - Hutagaol, Larasati; Negara, I Ketut Wija; Kartika, I Wayan Darya (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2024)
The development of beach tourism can be utilized to encourage positive changes to the community's economy through employment opportunities, increasing income, and improving the quality of life of the community. This research was conducted at Penimbangan Beach, Bakti Seraga Village, Buleleng District. The potential attractions of Penimbangan Beach are diving, beach recreation, and swimming. Data collection to determine the condition of beach tourism through the carrying capacity of the area and development strategies carried out in February 2024. This study aims to determine the carrying capacity of the tourist attraction area and tourism development strategy of Penimbangan Beach. The method used is descriptive method with qualitative and quantitative approaches, and data analysis using SWOT analysis and DDK calculation. Based on the calculation of DDK on three tourist activities, namely diving as many as 2 people / day, beach recreation as many as 202.88 people / day, and swimming 30.72 people / day. The results of the SWOT analysis obtained an aggressive strategy, namely increasing visitor comfort while conducting tourism activities and preserving nature by educating visitors about the importance of maintaining cleanliness, increasing promotion through information media such as websites, videos, brochures, posters containing information about the beauty of the underwater and the benefits of black sand, adding facilities and infrastructure to increase the interest of tourist visits, and building tourism facilities.